The development of Philippine piano literature - Galang, Abelardo Goco
This work proposes the analysis of Philippine piano literature through "Five waves of stylistic development". While there exist theses and dissertations focusing on specific genres and composers, no attempt hitherto has been made to trace the historical development of Philippine piano literature.